Brush-structured sulfur–polyaniline–graphene composite as cathodes for lithium–sulfur batteries. (December 2019) - Liu, Heguang; Jing, Ruixuan; You, Caiyin; Zhong, Qifeng
Abstract: Abstract : In this work, the authors report a facile method for the preparation of brush-structured nanocomposites of sulfur–polyaniline–graphene oxide (S–PANI–G) that were used for cathode materials of lithium–sulfur batteries (LSBs). The morphology and structure of composite were studied by x-ray photoelectron microscopy, transmission electron microscopy, scanning electron microscopy, and x-ray diffraction analysis. The nanocomposites exhibited good electrochemical performance involving good rate performance, high capacity, and promising cycling stability. The good performance of S–PANI–G results from the synergistic effect of sulfur, polyaniline, and graphene oxide. The composite and method reported here pave the way for the design and synthesis of novel cathode materials for LSBs.